An act to prevent the transfer or conveyance of the estates and property of all persons ... guilty of treason ([publisher not identified], 1777)
Two acts from 1777. One act prevents the transfer or conveyance of the property from an accused person of treason to another and the deeds, grants and other conveyances would be null and void. Another act deals with speculators and to encourage fair dealings and punish sharpers and oppressors.